THE ROLE OF DESCRIPTIVE GEOMETRY IN THE DEVELOPMENT OF STUDENTS’ COGNITIVE COMPETENCIES (American Journal of Technology and Applied Sciences, 2025)
This article explores the didactic, methodological, and cognitive potential of the subject of descriptive geometry in the formation and development of students' cognitive competencies. Within the framework of modern education, where analytical thinking, independent problem-solving, and spatial imagination are among the essential skills, descriptive geometry serves not only as a technical discipline but also as a pedagogical tool for cognitive enhancement. The study is based on theoretical analyses of psychological and educational literature, integrating classical cognitive development theories by Vygotsky, Piaget, and Bloom with modern instructional strategies. The article examines how the structural elements of descriptive geometry—such as projections, views, sections, and abstract modeling—contribute to the development of visual logic, mental manipulation, and spatial cognition. It also evaluates the role of computer-aided design (CAD) technologies in enhancing digital graphic thinking and interactive learning. Recommendations are proposed for curriculum reform, interdisciplinary integration, and competency-based instructional design. The findings confirm that descriptive geometry plays a crucial role in shaping intellectual flexibility and cognitive maturity among students in architecture, engineering, and design disciplines.